Interacción entre la razón y las emociones en el ser humano según Santo Tomás de Aquino (2008)
This paper approaches a well defined aspect of Aquinas’ thought: the mutual influence between reason and emotions; that is, how human reason influences human emotions and vice versa. The subject itself is interesting, but also extremely important for psychology, ethics and pedagogy. Key words Saint Thomas Aquinas, reason, emotions, psichology, ethics, pedagogy.